Lawrence of Arabia : a film's anthropology - Caton, Steven Charles, 1950- (University of California Press, 1999)
Combining ethnography, film criticism, and his extensive knowledge of the Middle East, Steven C. Caton presents an innovative and fascinating examination of the classic film, 'Lawrence of Arabia'.